Fear of cyber-identity theft and related fraudulent activity - Roberts, Lynne; Indermaur, D.; Spiranovic, C. (Routledge, 2013)
Identity theft and related fraudulent activities affect approximately one in twenty-five adults each year across western societies. The Internet provides a new avenue for obtaining identity tokens and identifying information and increases the scale on which identity theft can be perpetrated. Recent research has suggested that fear of these types of crimes now matches or exceeds the fear of traditional place-based crimes, and has the potential to curtail online activities and hinder the further development of e-commerce applications. In this article, we conduct exploratory research identifying predictors of fear of cyber-identity theft and related fraudulent activities, based on the analysis of items included in the Australian Survey of Social Attitudes (2007). Fear was predicted by a generalized fear of crime component and a specific Internet exposure component. Traditional predictors of fear of crime were insignificant or weak predictors, highlighting the need for further research.